ركن االختصاص في القـرار االداري - بركات أسامة - بن عثمان رشدي (المسيلة, 2023)
يعتبر ركن االختصاص أحد أهم األركان األساسية التي يقوم عليها القرار اإلداري، كونه يتعلق بالنظام العام، كما أنه يعد نتيجة من نتائج مبدأ الفصل بين السلطات، ويترتب على تخلفه تعيب القرار اإلداري بعيب يسمى عيب عدم االختصاص، ويتسم القرار بهذه الصفة لصدوره من غير السلطة المخولة قانونا بإصداره. وقد تناولت هذه الدراسة أن فكرة االختصاص تتحدد بأربعة عناصر، العنصر الشخصي، العنصر الموضوعي وكذا العنصر المكاني والعنصر الزماني، باإلضافة إلى جميع المسائل المرتبطة بركن االختصاص والمؤثرة فيه كالتفويض، الحلول، واإلنابة التي يجب على اإلدارة العامة مراعاتها عند إصدارها للقرار اإلداري. الكلمات المفتاحية: ركن االختصاص، القرار اإلداري، عيب عدم االختصاص. Summary: The jurisdiction pillar is considered one of the most important basic pillars on which the administrative decision is based, as it is related to public order, and it is also a result of the results of the principle of separation of powers, and its failure entails defecting the administrative decision with a defect called the defect of lack of jurisdiction, and the decision is characterized by this characteristic because it was issued without the authorized authority legally issuing it. This study has dealt with the fact that the idea of jurisdiction is determined by four elements, the personal element, the objective element, as well as the spatial element and the temporal element, in addition to all issues related to the pillar of jurisdiction and affecting it, such as delegation, solutions, and delegation that the public administration must take into account when issuing the administrative decision. Keywords: jurisdiction corner, administrative decision, defect of lack of jurisdiction.
Keywords: ركن االختصاص، القرار اإلداري، عيب عدم االختصاص.